Hepatitis B virus drug resistance mutation detection by pyrosequencing method - Toh, Kim Pern. (2013)
Monitoring of drug resistance mutations in Hepatitis B virus (HBV) is critical for the management of chronic HBV infection treatment. It is important to use a system that is sensitive and specific in its detection. In this report, we proposed pyrosequencing as a method for the detection of 13 mutation points in HBV reverse transcriptase gene. Statistical results showed that the assay could detect mutant virus population of as low as 5%, and for 10% mutant virus the coefficients of variation ranged from 2.99 –11.92%. The data also had a strong linear relationship when plotted against the percentage of mutant virus variant with correlation coefficient R2 values ranging from 0.9983 to 0.9996. Clinical results showed that resistance to the drug lamivudine is the most common among Singaporean patients. When 46 samples with results for INNO-LiPA HBV DR v.2 was compared with the assay, 29 (63%) samples had disconcordant results. 8 of these disconcordant samples were sent for direct PCR sequencing, and it was proven that the results from pyrosequencing were accurate. This assay has a lower reagent cost, increased sensitivity and specificity when compared with commercial assays.